Symbol. Między słowem a obrazem (tłum. P. Mikulska) - RAVASI, Gianfranco; MIKULSKA, Patrycja (Ethos. Kwartalnik Instytutu Jana Pawła II KUL, 2012)
There are many who express regret that Christianity, as religion of the Word, suffers depreciation due to the fact that the prevailing culture is overloaded with images, ignoring or even suppressing the word and the values it stands for. In this article, the author proposes considerations on the notion of the symbol as ideally uniting the image and the word and thus creating for both the opportunity for maximum expression. The analysis is set in the context of exegetical research and provides the illustrative material that the reader can use as a starting point for their own reflection on culture. By re-establishing the elevated status of the symbol, it is possible to avoid a seeming antagonism between the image and the word, at the same time preserving and emphasizing the vitality of Christianity in the context of contemporary culture. Translated by Patrycja Mikulska